Opera, Power and Ideology by Vlado Kotnik - Dragana Antonijević (University of Belgrade, 2016)
Vlado Kotnik. Opera, Power and Ideology. Anthropological Study of a National Art in Slovenia. 2010. Peter Lang, Internationaler Verlag der Wissenschaften